Capturing microfibers – marketed technologies reduce microfiber emissions from washing machines. (February 2019) - McIlwraith, Hayley K.; Lin, Jack; Erdle, Lisa M.; Mallos, Nicholas; Diamond, Miriam L.; Rochman, Chelsea M.
Abstract: Microfibers are a common type of microplastic. One known source of microfibers to the environment is domestic laundering, which can release thousands of fibers into washing machine effluent with every wash. Here, we adapted existing methods to measure the length, count and weight of microfibers in laundry effluent. We used this method to test the efficacy of two technologies marketed to reduce microfiber emissions: the Cora Ball and Lint LUV-R filter. Both technologies significantly reduced the numbers of microfibers from fleece blankets in washing effluent. The Lint LUV-R captured an average of 87% of microfibers in the wash by count, compared to the Cora Ball which captured 26% by count. The Lint LUV-R also significantly reduced the total weight and average length of fibers in effluent. While further research is needed to understand other sources of microfiber emissions, these available technologies could be adopted to reduce emissions from laundering textiles. Highlights: Introducing a method to measure microfibers by length, count and weight Two microfiber-capturing technologies tested: Cora Ball and Lint LUV-R filter Both technologies reduce microfibers in washing machine effluent by count The Lint LUV-R filter reduced microfibers in washing machine effluent by weight